LINC01133 inhibits breast cancer invasion and metastasis by negatively regulating SOX4 expression through EZH2. Issue 11 (26th September 2019) - Song, Zhiwang; Zhang, Xia; Lin, Yun; Wei, Youzhen; Liang, Shujing; Dong, Chunyan
Abstract: Mounting evidence highlights long non‐coding RNAs (lncRNAs) as crucial regulators in multiple types of biological processes and contributing to tumourigenesis. LINC01133, located in chromosome 1q23.2, was a recently identified novel lncRNA with a length of 1154nt. It was involved in the development of colorectal cancer and non‐small cell lung cancer. However, its clinical relevance, biological functions and potential molecular mechanism in breast cancer are still unclear. In this study, we found that the LINC01133 expression was significantly down‐regulated in breast cancer samples and was associated with progression and poor prognosis of breast cancer. Further experiments demonstrated that overexpression of LINC01133 inhibited invasion and metastasis in breast cancer both in vitro and in vivo. Mechanistic investigations revealed that LINC01133 repressed SOX4 expression by recruiting EZH2 to SOX4 promoter. Moreover, rescue experiments further confirmed that LINC01133 functional acted as an anti‐oncogene, at least partly, via repressing SOX4 in breast cancer. Taken together, these findings imply that LINC01133 could serve as a novel prognostic biomarker and potential therapeutic target for breast cancer.